2014
DOI: 10.1167/iovs.14-14748
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography Parameters in Phacomorphic Angle Closure and Mature Cataracts

Abstract: Anterior chamber depth, ACA, AOD750, and LV are powerful indicators in differentiating phacomorphic angle closure eyes from those with mature cataract and their fellow eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
5
32
0
Order By: Relevance
“…4,6,13,27 In a cross-sectional study by Nongpiur et al, 9 LV was found to be one of the strongest predictors of PACG. In eyes with greater LV, the iris is pushed more anteriorly, leading to a crowded angle.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…4,6,13,27 In a cross-sectional study by Nongpiur et al, 9 LV was found to be one of the strongest predictors of PACG. In eyes with greater LV, the iris is pushed more anteriorly, leading to a crowded angle.…”
Section: Discussionmentioning
confidence: 95%
“…Mansouri et al 13 did not find any significant difference between mature cataracts and phacomorphic angle closures in terms of AL. They proposed that the anterior segment dimensions of the eye might play a more important role in the development of phacomorphic angle closure.…”
Section: Figurementioning
confidence: 86%
See 2 more Smart Citations
“…We believe that much of the hypotensive effect arising from lens extraction is related to the anatomical configuration of the anterior chamber and the degree of angle opening, in addition to the functional reserve of the trabecular meshwork. In this context, eyes with shallower chambers, greater influence of the lens component (greater lens vaults), narrower angles without extensive synechiae, and good trabecular function could most benefit from cataract surgery in terms of IOP reduction (21,22) . This seems to explain the modest effect of phacoemulsification in controlling IOP in eyes with open-angle glaucoma.…”
mentioning
confidence: 99%